ANALYSIS OF INDONESIAN COAL EXPORTS TO THE TOP LARGEST IMPORTING COUNTRIES - Putri Alif Sya’diyah; Aris Soelistyo; Muhammad Khoirul Fuddin (Jurnal Ilmiah Bisnis dan Ekonomi Asia)
Indonesia with abundant natural resources optimizes its superior commodities in trade in the global market. This lesson aims to analyze the factors that affect the value of Indonesian coal exports as a superior commodity. The research method uses panel data regression analysis in 2009 - 2022 and a cross-section of the ten largest destination countries for Indonesian coal exports. The comes about appeared that in part the sum of production, Indonesian GDP, and reference coal cost had a noteworthy and positive impact on trade value, framework had a noteworthy and negative impact on send out value, GDP of bringing in nations and swelling had no noteworthy and positive impact on send out value, trade rate, the populace of bringing in nations had no noteworthy and negative impact on send out value and at the same time the free factors together had an impact on the subordinate variable. This research can be used as a strategic guide in increasing production, maintaining exchange rate stability, encouraging economic growth, and improving infrastructure to support Indonesia's coal export sector. The shortcomings of this lesson are that it does not consider data stationarity and influence in the short and long term.